ПРАВОВІ ТА СОЦІАЛЬНІ АСПЕКТИ ІМПЛЕМЕНТАЦІЇ РЕСПУБЛІКОЮ ПОЛЬЩА КОНВЕНЦІЇ ПРО ПРАВА ІНВАЛІДІВ - Borski, М. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2018)
Among the many rights guaranteed by the United Nations Convention on the Rights of Persons with Disabilities, special attention should be paid to the right of persons with disabilities to independent living and integration into society, which is enshrined in Art. 19. This right extends to all, regardless of their age, abilities, disability category or mental health problems. In practice, this means that the state needs to take effective measures to promote the integration of people with disabilities and their participation in public life. In the article, the author tried to answer the question whether the Polish state has taken effective measures to assist disabled people in their full integration and participation in public life. Therefore, attention was drawn to the need for deinstitutionalization of social assistance, pointing at the same time to two important tools through which it can be implemented in practice. "De-institutionalization" means «the entire process of planning for the transformation and diminishing of the importance of inpatient facilities or their elimination, while simultaneously providing other types of various childcare services based on human rights standards and results-oriented». The realization of the right of every person to live in his usual environment requires the creation of conditions that would allow everyone, including the disabled, to enjoy this right. It is about providing decent living and housing by supporting disabled people in their previous place of residence. Many years of experience show that institutional assistance meets life’s needs, but it is isolated from the previously known social and physical environment, and the quality of life in these institutions is much worse than the high quality of services provided at the local community level. This means that deinstitutionalization of forms of support for people with disabilities can prevent the social isolation of these people. REFERENCES